SPR Biosensing MUA/Poly-L-lysine Platform for the Detection of 2,4-Dinitrophenol as Small Molecule Model System - Daza Millone, Maria Antonieta (2016)
Surface Plasmon Resonance assays are being developed as alternative biodetection methods for a great number of pesticides and toxins. These substances typically have low molecular weight, making it necessary to perform competitive inhibition immunoassays. In most of the cases, the strategy is to immobilize a protein derivative of the analyte, which usually involves the appearance of nonspecific protein binding which limits the detection range of the assay. In this work we present results of a poly-L-lysine (Au-MUA-PLL) based sensor platform for quantitative determination of 2,4-dinitrophenol as model system for small molecular weight substances detection. The prepared sensor chip was characterized by means of Atomic Force Microscopy, Surface Plasmon Resonance, and Surface Enhanced Raman Spectroscopy. Experiments verified the absence of nonspecific protein adsorption to Au-MUA-PLL surfaces and the improvement of the competitive inhibition assays performance in comparison with single and mixed thiol self-assembled monolayers. The possibility of directly immobilizing 2,4-dinitrophenol to the poly-L-lysine containing platforms leads to an improvement in the detection of the soluble analyte by the competitive inhibition assay avoiding undesirable nonspecific protein adsorption. Therefore, Au-MUA-PLL surfaces constitute a suitable alternative for quantitative detection of small molecules when nonspecific adsorption cannot be avoided.